PENGARUH MODEL COOPERATIVE LEARNING TIPE STUDENT TEAMSACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR LEMPAR CAKRAM - Galih Prio Utomo; Edi Purnomo; Andika Triansyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimed to determine the effect of model cooperative learning Type Student Teams Achievement Division learning outcomes towards of disc throwing on the learners of SMAK Abdi Wacana Pontianak. The method used was the experimental method, the study design used pre-experimental design, and the study design used the design of one group pretest-posttest design. The study population was all students of class XI (IPS 1, IPS 2, and IPA 3), SMAK Abdi Wacana Pontianak, 2018/2019 as many as 92 students. The research sample was 20 students. The data collection technique used was the disc throw test. Were analyzed data by descriptive analysis and using the t-test (influence test). From the results of the research conducted, it can be concluded that there was a significant influence on the model cooperative learning type Student Teams Achievement Division learning outcomes towards on disc throwing of SMAK Abdi Wacana Pontianak. The results of the t-test analysis show that the value of tcount (9.211) and t table (2,093) or (9.211> 2,093). The magnitude of the percentage of influence given by learning using the model cooperative learning type Teams Achievement Division learning outcomes towards on disc throwing of SMAK Abdi Wacana Pontianak students was 39.62%.Keywords : Cooperative Learning, Disc Throwing, Learning Outcomes, Student Teams Achievement Division.